2012
DOI: 10.1074/jbc.l112.394411
|View full text |Cite
|
Sign up to set email alerts
|

Reply to Rapaport: The Mitochondrial Protein OM45 Is Exposed to the Cytosol

Abstract: This is a response to a letter by Rapaport (1).We thank Dr. Rapaport for his interest in our studies. Yaffe et al. (2) didn't present experimental data on the topology of the protein; instead they cite Riezman et al. (3) ("Previous studies…indicate that OM45 is an integral membrane protein with the bulk … exposed to the cytoplasm."). However, Riezman et al. (3) state: "We conclude … that this 45-kDa protein is exposed to the intermembrane space in intact mitochondrion…."Besides immunological data, the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…Om45 has originally been described as an outer membrane protein, facing into the cytosol ( 87 , 88 ), although IMS localization has also been reported ( 89 ). We found that Om45 extensively cross-links to porin, which is in accordance with a previous biochemical study ( 89 , 110 ). We also show that Om45 extensively cross-links to Nde1 suggesting that it forms a complex.…”
Section: Discussionsupporting
confidence: 93%
“…Om45 has originally been described as an outer membrane protein, facing into the cytosol ( 87 , 88 ), although IMS localization has also been reported ( 89 ). We found that Om45 extensively cross-links to porin, which is in accordance with a previous biochemical study ( 89 , 110 ). We also show that Om45 extensively cross-links to Nde1 suggesting that it forms a complex.…”
Section: Discussionsupporting
confidence: 93%
“…To detect RNAs near the mitochondrial outer membrane, we inserted PUP-2 downstream of the OM45 gene, resulting in an Om45p–PUP-2 chimera, which we refer to as “Mito-PUP” hereafter. Om45p is predicted to be cotranslationally inserted into the mitochondrial membrane with its C-terminal PUP-2 domain in the cytosol ( 37 42 ) ( Fig. 3 A ).…”
Section: Resultsmentioning
confidence: 99%
“…( A ) Architecture of Mito-PUP. PUP alone was fused to the cytosolic C-terminal end of the mitochondrial membrane protein, Om45p ( 37 42 ). ( B ) Confocal localization of Mito-PUP fluorescence (green) and the mitochondrial marker, Tom70p-mCherry ( 31 ) (red), including fluorescence intensity across a line that bisects the cell (below).…”
Section: Resultsmentioning
confidence: 99%
“…40,4648 After identification of the a-helical membrane proteins of the TOM complex, the specific complex formation between β-barrel membrane proteins and a-helical membrane proteins was regarded as a special case. Meanwhile the porin β-barrel membrane protein was found to interact with the a-helical membrane proteins Om14 and Om45 and the β-barrel protein Mdm10 interacts as subunit of the ER-mitochondria encounter structure (ERMES) with the a-helical outer membrane proteins Tom7 and Gem1(Miro-1) 23,2527,49…”
Section: Discussionmentioning
confidence: 99%